Efficacy and safety of ustekinumab in Japanese patients with severe atopic dermatitis: a randomized, double‐blind, placebo‐controlled, phase II study. (27th June 2017) - Saeki, H.; Kabashima, K.; Tokura, Y.; Murata, Y.; Shiraishi, A.; Tamamura, R.; Randazzo, B.; Imanaka, K.
Summary: Background: Ustekinumab, a fully human monoclonal antibody against interleukin‐12/23, may potentially be effective for severe atopic dermatitis (AD) treatment. Objectives: To evaluate efficacy and safety of ustekinumab 45 mg and 90 mg in patients with severe AD. Methods: In this randomized, placebo‐controlled, phase II study, Japanese patients (aged 20–65 years) with severe or very severe AD entered a 12‐week double‐blind treatment period during which they received (1 : 1 : 1) ustekinumab 45 mg, 90 mg or placebo subcutaneous injections at weeks 0 and 4, with follow‐up until week 24. The primary efficacy end point was percentage change from baseline in Eczema Area and Severity Index (EASI) score at week 12. Major secondary efficacy end points included the proportion of patients achieving EASI 50, EASI 75, Investigator's Global Assessment score 0–1, change from baseline Atopic Dermatitis Itch Scale and Dermatology Life Quality Index. Results: A total of 79 patients were randomized [ustekinumab 45 mg ( n = 24), 90 mg ( n = 28), placebo ( n = 27)]. Ustekinumab treatment showed nonsignificant improvement in least square mean change from baseline EASI score at week 12 [45 mg: –38·2%, 95% confidence interval (CI) –21·02–19·51; P < 0·94 and 90 mg: –39·8%, 95% CI –21·84–17·14; P < 0·81] vs. placebo (–37·5%). A nonsignificant improvement in major secondary efficacy end points was observed in both ustekinumab groups vs. placebo. The most common treatment‐emergent adverse events were nasopharyngitis and worsened AD (higher in placebo vs. ustekinumab groups). Conclusions: Ustekinumab 45 mg and 90 mg did not demonstrate meaningful efficacy in Japanese patients with severe AD. The treatment was generally well tolerated. Abstract : What's already known about this topic? There are reports suggesting the involvement of T helper 17 cells in the pathogenesis of atopic dermatitis (AD). Several case studies have reported therapeutic benefits of ustekinumab in patients with severe AD, while a few studies have failed to show the benefits. What does this study add? Ustekinumab 45 mg and 90 mg did not demonstrate meaningful efficacy in Japanese patients with severe AD. Ustekinumab treatment was generally well tolerated in Japanese patients with severe AD. Respond to this article Linked Comment:  Samuel and Reynolds. Br J Dermatol 2017;177 :339–341